2014
DOI: 10.1007/s00213-014-3684-1
|View full text |Cite
|
Sign up to set email alerts
|

Delta-9-tetrahydrocannabinol, neural oscillations above 20 Hz and induced acute psychosis

Abstract: RationaleAn acute challenge with delta-9-tetrahydrocannabinol (THC) can induce psychotic symptoms including delusions. High electroencephalography (EEG) frequencies, above 20 Hz, have previously been implicated in psychosis and schizophrenia.ObjectivesThe objective of this study is to determine the effect of intravenous THC compared to placebo on high-frequency EEG.MethodsA double-blind cross-over study design was used. In the resting state, the high-beta to low-gamma magnitude (21–45 Hz) was investigated (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 88 publications
3
18
0
Order By: Relevance
“…Acute adverse effects of cannabis consumption include disordered thoughts and cognitions (including paranoia), a sense of depersonalisation, fear of dying, and an impending feeling of panic (Ashton, 2001). D'Souza et al 2004 are also related to increases in high frequency brain oscillations (Nottage et al, 2015).…”
Section: Acute Outcomesmentioning
confidence: 99%
“…Acute adverse effects of cannabis consumption include disordered thoughts and cognitions (including paranoia), a sense of depersonalisation, fear of dying, and an impending feeling of panic (Ashton, 2001). D'Souza et al 2004 are also related to increases in high frequency brain oscillations (Nottage et al, 2015).…”
Section: Acute Outcomesmentioning
confidence: 99%
“…Morrison and others at King's College London [48] documented decreased theta coherence in the frontal lobes bilaterally following THC administration, which correlated with positive psychotic symptoms. More recently, the same team [49] utilized a double blind design to demonstrate a shift towards higher frequency bands following IV THC administration, correlating with positive symptom score on Positive and Negative Symptom Scale (PANSS), a standard measure of psychotic presentations.…”
Section: Cannabis and Psychosismentioning
confidence: 99%
“…Research has constantly shown that sensorimotor gating is normal in DVD deficient rats [13,14]. There is one exception, PPI was enhanced after administration of delta- 9-terohydrocanabinol [29]; a psychoactive substance that has potential to induce psychotic symptoms [30]. Thus, DVD-deficiency can influence, but alone is not sufficient to cause, impairment in attention when assessed using PPI.…”
Section: Cognitive Phenotypesmentioning
confidence: 99%